Monitoring dan Kontrol Gas CO Dalam Ruangan Berbasis Pemrograman LabVIEW dan Mikrokontroler - Andrizal Andrizal; Yul Antonisfia (Teknik Elektro Politeknik Negeri Padang, 2021)
Carbon dioxide is gas produced by industrial pollution and motor vehicle exhaust emissions. The air is declared clean and healthy for human activities if the CO level does not exceed 15 ppm. Industrial pollution or motor vehicle pollution does not only pollute the outdoor air, but it is very likely to pollute the indoor air. For this reason, a system that is able to monitor and control CO levels in the room has been designed so that it is safe for users while doing this activities. The research stage is carried out by making a series of sensors to detect CO gas and then the sensor circuit is connected to the Arduino UNO microcontroller as an interface with a PC. The program used is LabVIEW programming as a neural programming for displaying Virtual Instruments as display media. The output system is an air purifier system that cleans the indoor air when the CO level is more than 15 ppm. Based on the results of trials and analyzes, the response of the sensor system is able to detect changes in CO gas within 7 seconds. The average monitoring of CO levels result when observed 30 times was 11.47 ppm. The air purifier response time is able to restore indoor CO levels to the maximum threshold of 15 ppm in the fastest time of 3 minutes and 22 seconds.